Endovascular evaluation of intracranial atherosclerotic stenosis in a sample of Egyptian patients presented with ischemic stroke - Mahmoud M Hassan; Khalid M Sobh; Mahmoud Galal; Salah I Ahmed; Sherief M Al Shazly; Abd Elaziz Shokry (Wolters Kluwer Medknow Publications, 2022)
Background and aim Intracranial atherosclerosis is an important etiology of ischemic stroke and is associated with multiple vascular risk factors. Endovascular evaluation is used for assessing patterns and distributions of intracranial atherosclerotic stenosis in a sample of Egyptian patients presented with ischemic stroke. Patients and methods A total of 50 patients with ischemic stroke or transient ischemic attack were included. Assessment of the state of cerebral vessels before the procedure was done by duplex ultrasound, magnetic resonance angiography, and/or computed tomography angiography to confirm any stenosis in intracranial vessels. Neurological assessment was done before and after the procedure using the National Institutes of Health Stroke Scale score. Digital subtraction angiography was done to evaluate the degrees and patterns of stenosis. Results A total of 50 participants (29 males and 21 females) were included. Their ages ranged from 30 to 78 years. The major risk factors were dyslipidemia (62.0%), hypertension (60.0%), diabetes mellitus (54.0%), smoking (48.0%), and atrial fibrillation (22.0%). The procedure was performed on 50 patients. A total of 39 (78.0%) patients had angiographic findings of vessel stenosis in either extracranial or intracranial vessels or both. In those 39 patients, 32 (64.0%) patients had arterial stenosis, and seven (14.0%) patients were found to have total occlusion. A total of 18 (36.0%) patients had angiographic findings of intracranial atherosclerotic stenosis. Of these 18 patients, 14 (28.0%) patients had arterial stenosis, and four (8.0%) patients were found to have total occlusion. The most common site of intracranial stenosis was middle cerebral artery (33.3%). Conclusion Endovascular evaluation of patients with ischemic stroke is yielding, informative, safe, and easy to be done.